Iridium complexes containing a PNP pincer ligand: syntheses, structural chemistry, and bond activations - Grüger, Nora; Wadepohl, Hubert; Gade, Lutz H. (European journal of inorganic chemistry, 2013)
The coordination chemistry of the monoanionic PNP pincer ligand 3,6-di-tert-butyl-1,8-bis[(diphenylphosphanyl)methyl]carbazole (Cbzdiphos) was investigated for different iridium(I) and iridium(III) complexes. Reaction of the protio ligand with [Ir(acac)(cod)] (acac = acetylacetonate; cod = 1,5-cyclooctadienyl) gave [(Cbzdiphos)Ir(cod)] (1). Upon hydrogenation the dihydrido complex [(Cbzdiphos)IrH2] (2) was obtained, and its reactivity in different organometallic transformations was examined. Treating 2 with ammonia afforded [(Cbzdiphos)IrH2(NH3)] (3), whereas treatment with diphenylacetylene (dpa) yielded the IrI compound [(Cbzdiphos)Ir(dpa)] (4) and trans-stilbene. Furthermore, the conversion with norbornene led to a reactive species, which activated C-H and C-Cl bonds. The reaction with THF gave a Fischer carbene [(Cbzdiphos)Ir=C(OC3H6)] (8) after double C-H bond activation, whereas treatment with benzene or chlorobenzene afforded the oxidative addition products [(Cbzdiphos)Ir(Ph)H] (5) and [(Cbzdiphos)Ir(Ph)Cl] (7).